Managing the Internet of Things : architectures, theories and applications - Huang, Jun; Hua, Kun (The Institution of Engineering and Technology, 2016)
The implementation and deployment of the Internet of Things (IoT) brings with it management challenges around seamless integration, heterogeneity, scalability, mobility, security, and many other issues. This comprehensive book explores these challenges and looks at possible solutions.
Keywords: Internet of things.; Telecommunication -- Data processing.; Ubiquitous computing.; Wireless sensor networks.; Telematics.; elektronické knihy; electronic books